Strangulated femoral Littre hernia in a 72-year-old female: A case report - Melanie B Mait; Samira M Hasan (International Journal of Abdominal Wall and Hernia Surgery)
Abstract Littre’s hernia is an uncommon hernia, in which a Meckel’s diverticula protrudes through a potential opening in the abdominal wall. Littre’s hernia is seen in less than 1% of patients with a Meckel’s diverticulum, and the most common sites of the hernia include inguinal, umbilical, and femoral. In this report, we present a case of a femoral Littre hernia in a 72-year-old female repaired with femoral herniorrhaphy and laparoscopic-assisted small bowel resection.